2001
DOI: 10.1088/0953-4075/34/12/309
|View full text |Cite
|
Sign up to set email alerts
|

The exact solution of the multistate Landau-Zener type model: the generalized bow-tie model

Abstract: The generalized bow-tie model (Yu N Demkov and V N Ostrovsky 2000 Phys. Rev. A 61 32705) is a particular generalization of the famous two-state Landau-Zener model widely used in atomic physics and beyond. It comprises an arbitrary number of states; the diabatic-potential curves are linear functions of time whereas the coupling matrix elements are constant. We derive a rigorous solution of the model by the contour integral method. The complete set of transition amplitudes is obtained by considering solution asy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
63
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(66 citation statements)
references
References 19 publications
3
63
0
Order By: Relevance
“…In its general form this problem is still unsolved, but a number of exact results for special choices of the matrices B and A were found [9][10][11][12][13][14][15][16][17][18][19]. In almost all available exact solutions the transition probabilities are expressed in terms of the genuine two-level LZ formula successively applied at each diabatic level intersection.…”
mentioning
confidence: 99%
“…In its general form this problem is still unsolved, but a number of exact results for special choices of the matrices B and A were found [9][10][11][12][13][14][15][16][17][18][19]. In almost all available exact solutions the transition probabilities are expressed in terms of the genuine two-level LZ formula successively applied at each diabatic level intersection.…”
mentioning
confidence: 99%
“…We found that, indeed, scattering matrix elements in all previously solved bipartite models satisfy (25). There is difference from Eq.…”
Section: Pure Gauge Phase Ansatzmentioning
confidence: 73%
“…However, in models with higher dimensions, scanning of a single parameter is usually insufficient to observe such points. We also found that some symmetric choices of parameters, for example LZ-chains with equal couplings and equidistant level slopes, do not generally satisfy (25) for N ≥ 4. So, our numerical investigation suggests that there are numerous solvable but still unknown bipartite models with asymmetric choices of parameters.…”
Section: Pure Gauge Phase Ansatzmentioning
confidence: 92%
“…for adiabatic evolution) is non-perturbative. Extensions to multi-level problems [27][28][29], many-body situations [22,[30][31][32][33], and non-linear LZ transitions [23,34,35] have been considered. When the LZ model becomes non-linear both the exponential dependence and the smoothness of P may be lost [23].…”
Section: B Landau-zener Problemmentioning
confidence: 99%